Pengembangan UMKM: Sinergi Sistem Informasi Akuntansi, Keandalan Laporan Keuangan, dan E-Commerce - Saraswati, Esti; Yuliarti, Lusi; Kristianto, Giovanny Bangun (Efektor, 2024)
This study aims to examine the effect of the use of accounting information systems on the development of MSMEs, evaluate the relationship between the use of accounting information systems and the reliability of financial reports, and investigate the effect of interest in adopting e-commerce on the development of MSMEs among MSME actors in North Purwokerto District. This study is associative with sampling using the Simple Random Sampling method involving a sample of 78 MSME actors who are members of a local association. Primary data were obtained through questionnaires. Data analysis techniques include descriptive statistical tests, data quality tests, and hypothesis testing. The hypothesis was tested using multiple linear regression analysis. The results of the study indicate that the use of accounting information systems and the reliability of financial reports partially do not have a significant effect on the development of MSMEs, while interest in implementing e-commerce partially has a significant effect on the development of MSMEs. Simultaneously, all independent variables have a significant effect on the dependent variable.